Diffusive gradients in thin films based on banana peel and moringa seeds binding gel disks for in situ measurement of Cd, Cu, Pb and Zn - Yabuki, Lauren N. Marques [UNESP]; Luko Sulato, Karen S. [UNESP]; Boniolo, Milena R. [UNESP]; Menegario, Amauri A. [UNESP]; Garcia, Marcelo Loureiro [UNESP] (Taylor & Francis Ltd, 2020)
Novel Diffusive Gradients in Thin Films (DGT) binding agents, Musa cavendishi banana peel (BP) and Moringa Oleifera seeds (MOS) immobilised in agarose gel, have been developed and validated for the determination of Cd, Cu, Pb and Zn in waters. The agarose-BP and agarose-MOS gel disks were characterised by Scanning Electron Microscopy, Energy Dispersive X-ray Spectrometry and Porosimetry by nitrogen adsorption. Elution of analytes from the binding agents was successfully performed with 2 mol L-1 HCl. The accumulation of Cd, Cu, Pb and Zn in DGT devices based on agarose-BP and agarose-MOS (DGT-BP and DGT-MOS) agreed well with the theoretical curves predicted by the DGT equation in synthetic solutions (500 mu g L-1 for each analyte). The uptake of DGT-BP and DGT-MOS for Cd, Cu, Pb and Zn was found to be independent of ionic strength of solutions up to 0.005 mol L-1 and for the entire studied pH range (from 3.5 to 8.0). Validation of DGT-BP and DGT-MOS methods was carried out by deploying the devices in spiked river water (the Corumbatai and the Piracicaba river). The recoveries obtained for the natural water matrices ranged between 40% and 150%. DGT-labile concentrations in situ for DGT-BP and DGT-MOS (performed in acid mine drainage) were also consistent with the values measured by conventional DGT-Chelex, albeit DGT-BP had a better binding capacity in acid drainage water. The predictions performed by chemical speciation modelling vMINTEQ were in general agreement for Pb using DGT-MOS (CDGT-MOS/C-dissolved 50% and Pb+2 (MINTEQ) species 41.9%) and for Cu using DGT-BP (CDGT-BP/C-dissolved 55% and Cu-MINTEQ(+2) species 62%). The proposed DGT-BP and DGT-MOS reaffirm the use of residual biomass as binding phase in the DGT technique, featuring low costs in production and 'green' technology approaches.
Keywords: Diffusive gradients in thin films; banana peel; moringa seeds; labile species; river water; acid mine drainage; passive sampler